Global Frequency and Geographical Distribution of Nighttime Streamer Corona Discharges (BLUEs) in Thunderclouds. Issue 18 (23rd September 2021) - Soler, S.; Gordillo‐Vázquez, F. J.; Pérez‐Invernón, F. J.; Luque, A.; Li, D.; Neubert, T.; Chanrion, O.; Reglero, V.; Navarro‐González, J.; Østgaard, N.
Abstract: Blue LUminous Events (BLUEs) are transient corona discharges occurring in thunderclouds and characterized by strong 337.0 nm light flashes with absent (or weak) 777.4 nm component. We present the first nighttime climatology of BLUEs as detected by the Modular Multispectral Imaging Array of the Atmosphere‐Space Interaction Monitor showing their worldwide geographical and seasonal distribution. A total (land and ocean) of ∼ 11 BLUEs occur around the globe every second at local midnight and the average BLUE land/sea ratio is ∼ 7:4. The northwest region of Colombia shows an annual nighttime peak. Globally, BLUEs are maximized during the boreal summer‐autumn, contrary to lightning which is maximed in the boreal summer. The geographical distribution of nighttime BLUEs shows three main regions in, by order of importance, the Americas, Europe/Africa and Asia/Australia. Plain Language Summary: Blue LUminous Events (BLUEs) are transient corona discharges occurring in thunderclouds and characterized by their distinct 337.0 nm light flashes with absent (or negligible) 777.4 nm component. We present the first two year nighttime climatology of BLUEs as detected by the Modular Multispectral Imaging Array of the Atmosphere‐Space Interaction Monitor on board the International Space Station that shows distinct worldwide geographical and seasonal distributions. Key Points: The first nighttime two‐year climatology of streamer corona discharges (blue luminous events) in thunderclouds is presented Globally, the rate of blue luminous events at local midnight is ∼11 per second Zonal and meridional distributions of blue luminous events peak in the northern tropic and the Americas, respectively